Customer market power and the provision of trade credit : evidence from Eastern Europe and Central Asia - Horen, Neeltje van, 1974- 1974- (The World Bank, 2007)
Statistics show that the sale of goods on credit is widespread among firms even when they are capital constrained and thus face relatively high costs in providing trade credit. This study provides an explanation for this by arguing that customers who possess strong market power are able to increase their customer surplus by demanding to purchase the goods on credit. This gain in customer surplus increases with the degree of asymmetric information between buyer and seller with respect to product quality. Therefore, firms that are perceived as risky are especially subject to the market power of the customer and have to sell their goods on credit. Using detailed firm-level data from a large number of firms in Eastern Europe and Central Asia, this study finds evidence consistent with this hypothesis. It finds a strong positive correlation between customer market power and trade credit provision. Furthermore, this relationship is especially strong when the supplier is more risky and in countries with limited financial sector development or a weak legal system